Professor Hansen and Keynesian Interest Theory - Nevin, Edward (Quarterly Journal of Economics, 1955)
Journal Article Professor Hansen and Keynesian Interest Theory Get access Edward Nevin Edward Nevin University College of Wales, Aberystwyth Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 637–641, https://doi.org/10.2307/1882001 Published: 01 November 1955